PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KPK DAN FPB SISWA SEKOLAH DASAR KELAS V - Yasaroh Nurbaya; Asep Samsudin (STKIP Subang, 2022)
This study aims to describe the use of problem-based learning models to improve the comprehension ability of KPK and FPB elementary school students in grade V. Subjects are grade V elementary school students located at Cirawa Mekar Elementary School in the Cirawa Mekar Kp. area, Cipatat District, West Bandung Regency with a total of 33 students. The method used is Mix Methods with a Sequntial Explanatory design. The sources obtained are quantitative data and qualitative data. Quantitative data processing techniques use test questions, while qualitative data use research instruments. The value (pretest) is 41.56. While the value (posttest) is 84.6. Based on the results of the N-gain test, the score g = 0.53 with a moderate category. And the percentage of effectiveness of the N-gain score obtained is a score of 56.64% with a fairly effective interpretation. The conclusion is that the use of the PBL model has increased in the capacity of understanding the KPK with the FPB of grade V elementary school students is quite effective to use.